The Precede-Proceed Model Concept Analysis on The Uptake of Visual Inspection with Acetic Acid Method (VIA) Test - Juwita, Linda; Ayu Prabasari, Ninda (Babali Nursing Research, 2023)
Introduction: The low awareness of women who already have knowledge about cervical cancer and early detection can have an impact on increasing cases of advanced cervical cancer, thereby increasing the incidence of death from cervical cancer. The purpose of this study was to analyze the relationship between the concept of the pre-process model and early detection of cervical cancer with acetic acid visual inspection. Methods: This research is a descriptive analytic study with a cross sectional approach, the population is all female volunteers at the Jagir Health Center. The sampling technique is purposive sampling. The samples in this study were those that met the inclusion criteria. The independent variables are education, employment, income, knowledge, attitude. The dependent variable is early detection of cervical cancer with acetic acid visual inspection with a total of 70 respondents. Results: Most of the respondents are highly educated (89%), most of the respondents are unemployed (91%), Most of the monthly income is < Minimum Wage (97%), knowledge of all respondents is good (100%), and attitudes of all respondents positive (100%). Conclusion: The results of the Chi-Square bacetic acid visual inspection riate test (p-value) show that all variables in the Precede-Proceed Model concept are > 0.05, which means that there is no relationship between education, employment, income, knowledge, attitudes and early detection of cervical cancer with acetic acid visual inspection.